Desain dan Implementasi Robot Mobile 4WD dan Aplikasi Smartphone sebagai Media Pembelajaran Robotik - Dwi Setiawan; Mufadol (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Technological advancements have significantly contributed to the robotics industry, yet mobility remains a challenge that can be addressed with mobile robots. In education, it is crucial to understand the basic principles of robotics and the use of related software and hardware. This research focuses on using a 4WD mobile robot as a learning tool. This robot offers flexibility and is easily controlled via a smartphone with built-in sensors. A smartphone application was developed using App Inventor, an open-source web-based development platform. The HC-05 Bluetooth module was used to connect the smartphone application with the 4WD robot. The goal of this research is to design innovative learning media to aid in understanding the concepts and control of the 4WD robot, as well as to increase students' interest and motivation in learning robotic systems. The results of the research demonstrated success in creating a 4WD robot prototype controllable via an Android smartphone. The distance between the Arduino and smartphone did not significantly affect the robot's movement, although communication was disrupted if the distance exceeded 10 meters. Directional control was achieved through the rotation of the right and left wheels, and sufficient power supply was needed to drive all wheels. Programming with C/C++ and Bluetooth communication functioned as planned. This innovative learning media is expected to help students understand and operate the 4WD mobile robot more effectively